Labrador, aerial view of mountains - Forbes, Alexander, 1882-1965 (1931)
(Series 27) Inland flight from head of Nachvak Fiord north at first to the west of the Central Range and then gradually crossing it, eventually reaching the drainage basin of the Eclipse River. Camera facing right front to line of flight. Grayscale